A Limited Role of p53 on the Ability of a Hexane Fraction of American Ginseng to Suppress Mouse Colitis. (30th July 2012) - Poudyal, Deepak; Cui, Xiangli; Mai Le, Phuong; Davis, Tia; Hofseth, Anne B.; Jin, Yu; Chumanevich, Alexander A.; Wargovich, Michael J.; Nagarkatti, Mitzi; Nagarkatti, Prakash S.; Windust, Anthony; Hofseth, Lorne J.
Abstract : Ulcerative colitis (UC) is debilitating and carries a high colon cancer risk. Apoptosis of inflammatory cells is a key mechanism regulating UC. We have recently shown that American ginseng (AG), and to a greater extent, a Hexane fraction of AG (HAG) can cause apoptosis and suppress mouse colitis through a p53-mediated mechanism. Here, we tested the hypothesis that HAG suppresses colitis through a p53 mechanism. We found only a limited impact of p53 in the ability of HAG to induce inflammatory cell apoptosis and suppress mouse colitis in vitro and in vivo . Finally, we asked whether HAG could cause cell cycle arrest of HCT116 colon cancer cells in vitro . Interestingly, HAG caused a G1 arrest of such cells independent of p53 status. Findings are significant because HAG suppresses colitis and associated colon cancer, and mutation in p53 is observed in most colitis-driven colon cancers. Therefore, HAG might be very effective in targeting the inflammatory cells and cancer cells since it induces apoptosis of inflammatory cells and cell cycle arrest in both p53 −/− and WT p53 colon cancer cells.